Strategi Peningkatan Customer Retention Melalui Digital Banking Innovation, Service Quality, dan Customer Satisfaction di Bank BRI - Sutarta Sutarta (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the role of Service Quality and Customer Satisfaction in mediating the effect of Digital Banking Innovation on customer retention. The research type used is explanatory associative research, aimed at understanding the relationships between variables. This study seeks to test hypotheses to validate or strengthen the hypotheses and support the underlying theory, which includes digital banking innovation, Service Quality, Customer Satisfaction, and customer retention. The study population comprises all customers of Bank BRI Jakarta Bintaro Branch, with a sample size of 170 customers selected using purposive sampling. The criteria for sample selection included customers who have been clients for at least one year and actively use the BRImo application to ensure respondents have sufficient experience and knowledge about the services being studied. Data collection was conducted using closed-ended questionnaires with a scale of 1 to 5, ranging from Strongly Disagree (SD) to Strongly Agree (SA), and data analysis was performed using Partial Least Square (PLS).  The results showed that Digital Banking Innovation significantly affects Service Quality and Customer Satisfaction but does not significantly affect customer retention. However, Service Quality and Customer Satisfaction were found to significantly affect customer retention. Additionally, digital innovation was found to influence customer retention indirectly through the improvement of Service Quality and Customer Satisfaction.